Decellularized rat submandibular gland as an alternative scaffold for dental pulp regeneration - Shi, Yuanyuan; Wang, Yingxin; Shan, Zhaochen; Gao, Zhenhua (Frontiers in Bioengineering and Biotechnology, 2023)
Decellularized extracellular matrix has been recognized as an optimal scaffold for dental pulp regeneration. However, the limited amount of native dental pulp tissue restricts its clinical applications. The submandibular gland shares some basic extracellular matrix components and characteristics with dental pulp. However, whether decellularized submandibular gland extracellular matrix (DSMG) can be used as an alternative scaffold for dental pulp regenerative medicine is unclear. Thus, we successfully decellularized the whole rat submandibular gland and human dental pulp, and then conducted in vitro and in vivo studies to compare the properties of these two scaffolds for dental pulp regeneration. Our results showed that extracellular matrix of the submandibular gland had great similarities in structure and composition with that of dental pulp. Furthermore, it was confirmed that the DSMG could support adhesion and proliferation of dental pulp stem cells in vitro. In vivo findings revealed that implanted cell-seeded DSMG formed a vascularized dental pulp-like tissue and expressed markers involved in dentinogenesis and angiogenesis. In summary, we introduced a novel accessible biological scaffold and validated its effectiveness as an extracellular matrix-based tissue engineering scaffold for dental pulp regenerative therapy.